Design of Airscrew Propeller as an Alternative Main Propulsion for Wing in Surface Effect (WiSE) A2C Using the Simplified Method Approach - Sasmito, Cahyo; Pujiwat, Rutma; Priatno, Dany Hendrik; Iskendar, Iskendar; Khoirudin, Muh Hisyam; Eskayudha, Dimas Bahtera (Mekanika: Majalah Ilmiah Mekanika, 2024)
This study focused on developing an airscrew propeller as an alternative propulsion system for the Wing in Surface Effect (WiSE) A2C, employing a rigorous and systematic scientific approach. The design and calculation methodology were grounded in the "simplified method" introduced by Hovey. This technique has proven effective for preliminary propeller design despite its reliance on several assumptions and simplifications. This method balances practicality with empirical data, offering a straightforward framework for generating initial design parameters without extensive computational demands. Although the simplified method has limitations, such as its dependence on empirical observations and reduced computational precision, it remains effective for developing foundational design concepts. The study leveraged this approach to create a propeller design that aligns with the aerodynamic and performance requirements specific to the WiSE A2C. The resulting design features an airscrew propeller with an RAF-6 airfoil profile and a diameter of 685 mm. The RAF-6 profile was chosen for its favorable aerodynamic characteristics, including a high lift-to-drag ratio, which is crucial for optimizing propulsion efficiency. This tailored design ensures compatibility with the operational environment of the WiSE A2C, enhancing its overall performance and stability while meeting specific aerodynamic goals.